2018
DOI: 10.1111/anec.12585
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prognostic role of Q waves and inverted T waves in the presenting ECG of STEMI patients

Abstract: Q waves and TWI predict adverse outcome, especially if both ECG features are present. Q waves and TWI predict similar one-year mortality. Extending the ECG analysis in STEMI patients to include both Q waves and TWI improves risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
5
0
5
Order By: Relevance
“…As it is simple, cost‐effective, and fast to use, great effort has been made to study its components for possible use in assessing the prognosis of patients with MI. The presence of pathologic Q waves on the first ECG usually predicts a poor prognosis, as this finding is related to myocardial necrosis (Thygesen et al., 2019) and cardiac mortality in patients undergoing fibrinolysis (Andrews, French, Manda, & White, 2000; Bar et al., 1987; Wong et al., 2006) or percutaneous coronary intervention (PCI) (Armstrong et al., 2009) (de Framond et al., 2019) (Koivula et al, 2019). Clinical outcomes such as heart failure (HF) and repeat revascularization have also been consistently related to the presence of Q waves on presentation, regardless of infarct location, adequacy of ST resolution, or early presentation (Kumar et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As it is simple, cost‐effective, and fast to use, great effort has been made to study its components for possible use in assessing the prognosis of patients with MI. The presence of pathologic Q waves on the first ECG usually predicts a poor prognosis, as this finding is related to myocardial necrosis (Thygesen et al., 2019) and cardiac mortality in patients undergoing fibrinolysis (Andrews, French, Manda, & White, 2000; Bar et al., 1987; Wong et al., 2006) or percutaneous coronary intervention (PCI) (Armstrong et al., 2009) (de Framond et al., 2019) (Koivula et al, 2019). Clinical outcomes such as heart failure (HF) and repeat revascularization have also been consistently related to the presence of Q waves on presentation, regardless of infarct location, adequacy of ST resolution, or early presentation (Kumar et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Aldrich et al [6] found that the number of leads with STE in AWMI was an important variable (r = 0.72) in predicting AMI size. Koivula et al [30], in their study on finding the prognostic role of Q-waves in STEMI patients, found that patients with Q-waves had larger infarct areas, which could explain the high one-year mortality seen in these patients. In their study on the prognostic Significance of ST-segment deviation in STEMI patients, De Luca et al [31] found that ST-segment deviation had good prognostic utility based on the area under the ROC curve (c = 0.73) in terms of one-year morality.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, patients with coronary no-reflow and/or delayed presentation after onset of symptoms — so called subacute MI — show signs of thromboinflammation and are characterized by worse clinical outcome ( 33 , 53 , 54 ). However, biomarkers other than Q waves or T wave inversion in electrocardiography ( 55 ) are currently not established to predict poor outcomes of patients with MI that is not timely reperfused. Our data indicate that TF phosphorylation of circulating monocytes may serve as a marker for patients at increased risk of developing IHF and adverse remodeling following MI.…”
Section: Discussionmentioning
confidence: 99%